Is the supply limited or is there no demand for women CEOs? - Óladóttir, Ásta Dís; Aðalsteinsson, Gylfi Dalmann; Christiansen, Þóra H. (Veftímaritið Stjórnmál og stjórnsýsla, 2019)
According to the World Economic Forum Global Gender Gap Report 2018 it will take more than 100 years to reach full gender equality in the world. Iceland has made the greatest progress towards closing the gender gap, or 85%. Yet no woman is CEO in any of the companies listed on the Icelandic stock exchange in 2019 and very few women sit on corporate boards. Women are more likely to be CEOs of small enterprises, with 1-10 employees, and in the case of larger enterprises, with 50 or more employees, women hold only 13% of the CEO positions. The study aims to explore the views of women in leadership positions regarding why no woman is CEO of a publicly traded company in Iceland and what actions are feasible to increase the number of women in top positions in Iceland. Women’s board membership and leadership positions in Icelandic companies are currently receiving a lot of attention and companies are encouraged to improve the gender ratio on boards and in the C-suite. The number of women on the boards and chairing the boards of listed companies is decreasing. To gain a clearer understanding of the situation, a survey was conducted among women leaders in Icelandic business. Responses from 186 women revealed that they feel that action must be taken, even legislative, such as enforcing gender quotas for executive positions, that organizational cultures and attitudes must change, that women need more opportunities and that men need to take more responsibility for family and child care. Samkvæmt niðurstöðu úttektar Alþjóðaefnahagsráðsins fyrir árið 2018 mun það taka heimsbyggðina rúmlega 100 ár að ná fullu jafnrétti. Samkvæmt úttektinni hefur Íslendingum tekist að jafna 85% af því kynjabili sem hér hefur ríkt og er Ísland það land sem hefur náð hvað lengst á sviði jafnréttis. Þrátt fyrir það gegnir engin kona stöðu forstjóra í skráðu félagi árið 2019 og afar fáar konur eru í framkvæmdastjórnum. Þá eru konur frekar framkvæmdastjórar í litlum fyrirtækjum, með 1-10 starfsmenn og konur eru í forsvari fyrir 13% stærri ...